Communication Skill, Student Engagement and Self-Efficacy: Flow on Effect on Student Online Learning - Susilowati, Nurdian; Mahmud, Amir; Sari, Puji Novita (Universitas Pendidikan Ganesha, 2022)
The transition from offline learning to online learning needs to be researched comprehensively. Accounting lessons, which were originally conducted face-to-face, were finally conducted online due to the COVID-19 pandemic. This study examines online learning using google meet on communication skills, student engagement, and student self-efficacy. The subjects of this study were students who took public sector accounting courses in their second year of study. Data collection was carried out using a google form distributed in public sector accounting classes. Paired t-test was used to analyze 120 student responses. The findings show that students' communication skills in online learning are increasing. Students can express their opinions and ideas using oral, written, and group presentations. However, online learning did not contribute to student engagement and student self-efficacy. They do not have clear learning targets because they do not have the pressure to be involved in online classroom activities. This implies that students have not realized that they should be involved in online learning. Other causes include low supervision by lecturers, and low awareness of students to learn. In addition, students are also unsure of their ability to do academic assignments. Based on these findings, this study provides significant implications for students and lecturers in choosing and using more appropriate online learning strategies to improve communication skills, student engagement, and self-efficacy.